PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA MELALUI KEPUASAN KERJA PADA PERANGKAT DESA PERANTE, AWAR-AWAR DAN ASEMBAGUS DI KECAMATAN ASEMBAGUS KABUPATEN SITUBONDO - Aprilia, Nurismil Khoir; Fandiyanto, Randika; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2025)
Human resource management is a critical component of any organization, aiming to attract, develop, motivate, and retain a qualified workforce. Therefore, a systematic and appropriate approach is needed to analyze the influence of work discipline, work environment, and organizational commitment on performance through job satisfaction among village officials in Perante, Awar-Awar, and Asembagus, Asembagus District, Situbondo Regency. The population in this study consists of village officials from Perante, Awar-Awar, and Asembagus. The sampling technique was determined using a probability sampling method. Data analysis and hypothesis testing were conducted using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) approach. The results of the direct effect hypothesis testing using SmartPLS 3.0 indicate that work discipline has a significant effect on job satisfaction; the work environment has a significant effect on job satisfaction; and organizational commitment also has a significant effect on job satisfaction. Furthermore, work discipline, work environment, and organizational commitment have a significant effect on employee performance. In addition, job satisfaction has a significant effect on employee performance. The results of the indirect effect hypothesis testing show that work discipline, work environment, and organizational commitment have a significant effect on employee performance through job satisfaction.